Chapter 8 ‘Phonographic awareness’ - Zucconi, Benedetta (Taylor & Francis, 2022)
Music has undergone a tremendous mediatization the last 100 years. Electrification and, later on, the digitization of music media have exposed music to an increased dissemination, both spatially – it can be heard almost everywhere – and temporally – one can listen to music almost anytime. This chapter aims to highlight and detail some fundamental changes and important transformations and displacements in everyday listening to recorded music as they first emerged. The macro level changes and transformations described by the concepts of mediatization and musicalization nevertheless depend on what happens at meso and micro levels. Recorded music in Sweden during the early decades of the century met with a “utilitarian” approach among audiences. In many ways, the change in attitude towards the gramophone and recorded music that can be traced in the reviews corresponds to transformations within the conceptual space.